Pathways to subsistence management in Alaska national parks: Perspectives of harvesters and agency staff - Kristen M. Green; Anne H. Beaudreau; Maija Katak Lukin; Nicole M. Ardoin (People and Nature, 2022)
Abstract Alaska Native peoples rely on harvest of animals and plants for cultural, nutritional, social and spiritual benefits. Contemporary management of these resources occurs under state and federal regulations; however, a long history of Indigenous stewardship precedes Western management systems and continues today. To illuminate the areas of compatibility and divergence among Indigenous and Western management systems, we examined multiple perspectives on subsistence management in Western Arctic National Parklands through interviews and focus group discussions with Indigenous (Iñupiat) communities and National Park Service (NPS) staff members in Alaska, USA. We examined perceptions about (1) communication and relationships between subsistence harvesters and NPS staff and (2) barriers to, and solutions for, improving subsistence management. We find various pathways to improving subsistence management from within the NPS structure that were shared between harvesters and management staff including addressing bureaucratic barriers and institutional structures, engaging the public in formal regulatory processes, enhancing community engagement and informal communication pathways, and bridging Indigenous knowledge and Western scientific knowledge systems. Pathways described by both harvesters and agency staff for improving management within the current governance system included fostering local and Indigenous representation in NPS management, minimizing NPS staff turnover, and changing the frequency and style of NPS engagement, especially through in‐person visits to rural villages. NPS staff described the need for increased funding, allocation of time and personnel to facilitate more outreach in villages; such shifts may help mitigate some of the perceived challenges associated with agency responsiveness to harvester needs. Harvesters and agency staff also discussed ways to perpetuate Indigenous stewardship practices outside of the federal (and state) governance systems. Advocating for self‐determination and ...